Analisis Desain Software Process Improvement Untuk Organisasi Pengembang Perangkat Lunak Skala Usaha Kecil - Ade Priyatna; Kukuh Panggalih; Deny Robyanto; Zico Pratama Putra (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
The development of software today in large and small organizations encourages every organization to develop and control in terms of development. Every organization in software development must grow and be able to improve itself, one of which is by handling advancement, if the company cannot do this. Therefore, the company will never be able to learn to take advantage of previous experience, so it will not be able to improve the quality of the existing process. Computer program Prepare Advancement can be done by referring to the CMMI (Capability Development Demonstrate Integration) made by SEI (Computer Program Designing Founded). SEI is a research center in the field of program designing, especially those related to procurement, engineering item lines, and prepare change. CMMI itself defines several levels of development, in order to go up to a higher level a number of processes must be carried out.